Evaluation of hepatoprotective activity of Boerhaavia diffusa against carbon tetrachloride induced liver toxicity in albino rats - Beedimani, Ravindra S.; Jeevangi, Santosh Kumar (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Modern allopathic medicine has very little to offer for the treatment of liver disorders in spite of consistent effort for new drug discovery. Hence, this study was conducted to elucidate the hepatoprotective activity of aqueous extract of traditional medicinal plant Boerhaavia diffusa against carbon tetrachloride (CCl4) induced toxicity in male albino rats. Methods: The hepatoprotective effect of the aqueous extracts of B. diffusa was evaluated by biochemical parameters such as serum alanine transferases (ALT), serum asparate transferases (AST), alkaline phosphatase (ALP), total serum bilirubin, and serum protein, and confirmed by histopathology of liver. The toxicant CCl4 was used to induce hepatotoxicity and silymarin were used as control drug. The aqueous extracts of B. diffusa were administered at the doses of 250 mg/kg/day and 500 mg/kg/day orally for 4 days. One-way analysis of variance was used for the statistical analysis of data. A probability value of p<0.05 was considered as significant. Results: Administration of B. diffusa at doses 250 and 500 mg/kg orally demonstrated hepatoprotective activity by preventing the increase of ALT, AST, ALP, and serum bilirubin and also confirmed by histopathology of the liver. The results were comparable to that of silymarin®. Conclusion: The results of this study confirmed the hepatoprotective activity of aqueous extracts of B. diffusa at doses of 250 mg/kg/and 500 mg/kg/against CCl4 induced hepatotoxicity in rats. However, the dose adjustments may be necessary to optimize the similar hepatoprotective efficacy in clinical settings.